An assessment of the fishery ordinances of the different coastal municipalities in the province of Iloilo, 1992-1998. - Almero, Flora B.
This research project is an assessment of the fishery ordinances of the different coastal municipalities in the Province of Iloilo. The study covers the fourteen (14) coastal municipalities of the Province namely; The Municipality of Anilao, Banate, Barotac Nuevo, Barotac Viejo, Batad, Carles, Concepcion, Dumangas, Estancia, Miagao, Oton, San Dionisio, San Joaquin and Tigbauan. The primary data were taken from the various municipal fishery ordinances of the different coastal municipalities under study, and the national fishery policies (RA 7160, PD 704, RA 8550). The researchers also emplyed field interviews with selected fisherfolk leaders as a source of first hand information concerning the recent situation of the fishery industry in their respective municipalities. It was found that: (1)the fishery industry in the Province of Iloilo is facing problems on overexploitation, overfishing, pollution, and habitat destruction; (2) the primary concern of the over-all policy mosaic for the fishery industry is the rehabilitation and protection of the coastal environment, the limitation of access to fishery resources comes as the secondary concern, while the protection of the rights of municipal fisherfolk appears in a very limited number of promulgations only; (3) generally the provisions in the over-all policy mosaic is consistent and complimentary both vis-a-vis the national fishery ordinances where the provisions belongs., Assessing the municipal fishery ordinances of the different coastal municipalities in the Province of Iloilo, it was found that the goal of the over-all policy mosaic is the promotion of sustainable development for the fishery industry so as to achieve food security in terms of fish.